European Concept of Research Infrastructure Development: the Possibility to Adapt the Experience of EU Scientific Infrastructures Formation for Use in Russia - E. V. Tarasova; A. A. Balyakin; D. V. Mun (Informaciâ i Innovacii)
In the article, the authors examine objects of scientific infrastructure, identify four types of large research infrastructures and analyze their functioning. Particular attention has paid to the study of practical experience and the specifics of organizing the work of research infrastructures in the EU, including the category of collective use of megascienceclass scientific complexes. The authors draw conclusions and recommendations on the use of the EU’s positive experience in this area for the organization of research infrastructure in Russia.